Efektivitas Pengawasan Pemilu Anggota DPR, DPD, dan DPRD Dalam Perspektif Pencegahan Pelanggaran Pemilu - Ismail Ismail (Jurnal Penelitian Hukum Legalitas, 2015)
The general elections are free and conducted regularly is one criterion that a political system can be said to be democratic, so that all countries implement a modern democratic elections. Methods used are normative juridical meth-od is a method of collecting data through library research, using secondary data which is generally a document. The analysis method used is qualitative analysis is a method to examine the quality of object and then translated at sentences so obtained discussion or exposure to systematic and understand-able. The results of this study were (1) Focus control the election of members of DPR, DPD and DPRD is to oversee all stages of election include the start of updating data, campaigns, polling and counting results up to the deter-mination of elected candidates. (2) Effective oversight would create election honest, fair and democratic, and can maintain the neutrality and integrity inside election.